2014
DOI: 10.1016/j.jacc.2013.10.061
|View full text |Cite|
|
Sign up to set email alerts
|

Early Increases in Multiple Biomarkers Predict Subsequent Cardiotoxicity in Patients With Breast Cancer Treated With Doxorubicin, Taxanes, and Trastuzumab

Abstract: Objectives The aim of this study was to determine if individual or multiple biomarkers are associated with cardiotoxicity in patients with breast cancer undergoing cancer therapy. Background Current methods to identify patients at risk for cardiotoxicity from cancer therapy are inadequate. Methods We measured 8 biomarkers in a multicenter cohort of 78 patients with breast cancer undergoing doxorubicin and trastuzumab therapy: ultrasensitive troponin I (TnI), high-sensitivity C-reactive protein (CRP), N-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
425
4
24

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 470 publications
(464 citation statements)
references
References 26 publications
11
425
4
24
Order By: Relevance
“…We found an elevation of hsTnT levels over upper normal limits in visit 1 and 2 and a significant difference between groups DD1 and DD2 at visit 2 that was consistent with evidence of cardiac damage. Ky et al [24], in an multicenter study in 78 breast cancer patients treated with doxorubicin and trastuzumab, found increases in troponin I levels at patients' 3-month visits that were associated with an elevated risk for cardiotoxicity. With a sampling protocol similar to our study, they found an increase in levels of troponins of identical magnitude to those found in our study (3.2 times the levels between baseline and first follow-up visit).…”
Section: Discussionmentioning
confidence: 99%
“…We found an elevation of hsTnT levels over upper normal limits in visit 1 and 2 and a significant difference between groups DD1 and DD2 at visit 2 that was consistent with evidence of cardiac damage. Ky et al [24], in an multicenter study in 78 breast cancer patients treated with doxorubicin and trastuzumab, found increases in troponin I levels at patients' 3-month visits that were associated with an elevated risk for cardiotoxicity. With a sampling protocol similar to our study, they found an increase in levels of troponins of identical magnitude to those found in our study (3.2 times the levels between baseline and first follow-up visit).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac troponins are well‐established markers of myocardial injury and appear to correlate best with incident cardiac dysfunction following chemotherapy. Three studies have reported that elevated and increasing troponin I following chemotherapy, particularly if such increase persists at 1 month after treatment,84 is associated with subsequent cardiac dysfunction as well as with lower likelihood of cardiac recovery in patients receiving trastuzumab 85, 86, 87. During treatment, negative cardiac troponin has a high negative predictive value; however, minute elevations can be commonly detected in patients following chemotherapy and have low positive predictive value 88.…”
Section: Monitoring For Cardiac Dysfunction During Her2‐targeted Therapymentioning
confidence: 99%
“…The recently published guidelines from the American Society of Clinical Oncology gives a moderate strength of recommendation for routine use of biomarkers and echocardiographic‐derived strain imaging for surveillance of cardiotoxicity, citing intermediate quality of evidence 53. Baseline N‐terminal pro–B‐type natriuretic peptide, a marker of hemodynamic stress, high‐sensitivity C‐reactive protein and growth differentiation factor‐15, markers of inflammation and oxidative stress, placental growth factor, a marker of angiogenesis, galectin‐3, a marker of fibrosis, soluble fms‐like tyrosine kinase receptor‐1, and others, have not shown significant association with future cardiac dysfunction 83, 85. Increases in N‐terminal pro–B‐type natriuretic peptide over time appear to correlate with changes in cardiac function; however, no thresholds have been established 87…”
Section: Monitoring For Cardiac Dysfunction During Her2‐targeted Therapymentioning
confidence: 99%
“…The risk of cardiotoxicity was not significantly associated with baseline levels of any of these biomarkers. However, the early changes in Tn-I and MPO, the combination of increasing biomarkers and finally the persistence of an increase in MPO beyond 3 months, were predictors of cardiotoxicity risk over the duration of doxorubicin/ trastuzumab therapy [61,62].…”
Section: Circulating Biomarkersmentioning
confidence: 99%
“…The authors propose a strategy that include, in addition to LVEF assessment, the GLS calculation and the baseline chosen biomarker measurement, all for prospective comparison with baseline data. Indeed, addition of monitored parameters via a multimodality surveillance strategy increases sensitivity of subclinical LV dysfunction detection [61,62]. However, only a few studies have explored the value of such a combined approach for the diagnosis and risk stratification of CTRCD ( Table 2, Fig.…”
Section: Cardiac Monitoring During Cardiotoxic Cancer Therapymentioning
confidence: 99%